Pengaruh Kebijakan Dividen, Ukuran Perusahaan, Struktur Modal terhadap Nilai Perusahaan pada Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2015-2017 - Munawarah Munawarah; Rosaulina Marpaung; Giabrella Octavia (Ekonomis: Journal of Economics and Business, 2020)
Research aims to analyze the effect of the variable Dividend Policy, Company Size, Capital Structure partially or simultaneously on Firm Value. The analytical method used in this method aims to examine the population and sample. The population in this study are companies listed in the mining Sector Listed on the Indonesia Stock Exchange 2015-2017. This sampling method uses a purposive sampling method, so that the population is 41 companies and after performing a standard sample determination that the research sample is 16 companies multiplied by 3 years, the number of observations is 48 companies in the mining sector listed on the Indonesian stock exchange in 2015-2017. The hypothesis in this study was tested using multiple linear regression. In this study, which was tested partially (T test) showed that the Dividend Policy variable did not have a significant effect on Firm Value, Firm Size had a significant positive effect on Firm Value, Capital Structure had no significant effect on Firm Value.